Antistatic polyolefin master batch and production process thereof

CN119286092AActive Publication Date: 2025-01-10DONGGUAN AURORA BIOTECHNOLOGY CO LTD
3 Cites 0 Cited by

Patent Information

Application Number
CN202411375325.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Polyolefin materials are prone to static electricity during friction or extrusion, resulting in electrostatic induction, electric shock and possible fire or explosion accidents. The existing antistatic masterbatches are not effective in tough materials and are difficult to meet actual needs.

Method used

Using polyolefin resin as the matrix, composite antistatic agent and modified toughening agent were added, and the combination of nanocarbon black, COF composite materials and maleic anhydride grafted polyethylene was prepared to produce permanent antistatic and excellent mechanical properties. antistatic polyolefin masterbatch.

Benefits of technology

The antistatic and mechanical properties of the material are improved, the sustainability and stability of the antistatic effect are ensured, the possibility of static accumulation is reduced, the toughness of the material is enhanced, and the static loss caused by friction or water washing is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and discloses an antistatic polyolefin master batch and a production process thereof. The polyolefin master batch is prepared from the following raw materials in parts by weight: 80 to 100 parts of polyolefin resin, 15 to 25 parts of a composite antistatic agent, 5 to 10 parts of a modified toughening agent, 1.5 to 3.5 parts of an antioxidant and 2 to 4 parts of a lubricating agent, according to the master batch, polyolefin resin is adopted as matrix resin, the antistatic property of the master batch is improved by adding the composite antistatic agent, and the mechanical property of the master batch is improved by adding the modified flexibilizer; wherein the composite antistatic agent adopts an organic-inorganic combination mode, so that the master batch has permanent antistatic performance; the modified toughening agent is obtained by modifying maleic anhydride grafted polyethylene, so that the mechanical property of the master batch is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to an antistatic polyolefin masterbatch and a production process thereof. Background Art

[0002] Polyolefin is a general term for all homopolymers, copolymers and mixtures of ethylene and propylene. It is widely used in electrical appliances, chemicals, food, machinery and transportation industries, and has become one of the indispensable chemical products in the national economy. Polyolefin itself is a highly insulating material. Under friction, extrusion and other conditions, it is very easy to generate and accumulate static electricity, which often causes static induction, electric shock and product production obstacles. In severe cases, it may even cause fire and explosion accidents, directly affecting the safety of production and use.

[0003] Therefore, when antistatic treatment is performed on polyolefin materials, antistatic masterbatch is generally added to improve the antistatic performance of the material, in order to reduce the surface resistance of plastic products and prevent various problems caused by static electricity accumulation, such as dust adsorption, electrostatic discharge, etc. This masterbatch is usually composed of carrier resin, antistatic agent and other additives, and is made into granules through a specific production process so that it can be added and used in the plastic processing process. In addition, considering that antistatic masterbatch may be used in materials with a certain toughness, researchers need to develop a polyolefin masterbatch with excellent antistatic and mechanical properties to meet actual needs. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides an antistatic polyolefin masterbatch and a production process thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: An antistatic polyolefin masterbatch comprises the following raw materials in parts by weight: 80-100 parts of polyolefin resin, 15-25 parts of composite antistatic agent, 5-10 parts of modified toughening agent, 1.5-3.5 parts of antioxidant, and 2-4 parts of lubricant; The polyolefin resin is polyethylene resin or polypropylene resin; The composite antistatic agent is prepared by the following steps: Step A1, dispersing nano carbon black in a 30wt% hydrogen peroxide solution, and ultrasonically treating it for 30-60min, then refluxing and stirring at 60°C for 24h, washing, drying, and collecting the pre-treated carbon black; adding γ-aminopropyltriethoxysilane to an ethanol solution and ultrasonically treating it for 15min, then adding the pre-treated carbon black and ultrasonically treating it for 1.5-2.5h, then refluxing and stirring it at 65-75°C for 5-7h, filtering, washing, and drying to obtain modified carbon black; Step A2, adding p-phenylenediamine, 2,5-diaminobenzoic acid and triethylamine to N,N-dimethylformamide and dispersing them uniformly, then adding cyanuric chloride and modified carbon black and ultrasonically dispersing them for 30 minutes, then transferring them to an autoclave and reacting them at 100-120° C. for 10-16 hours, washing and drying, to obtain a carbon black / COF composite material; Step A3, dispersing the carbon black / COF composite material, propylene oxide and tetrabutylammonium bromide in N,N-dimethylformamide, introducing nitrogen for 10 minutes, reacting under nitrogen at 80-90° C. for 2-3 hours, then cooling to room temperature, adding ethylene oxide and potassium hydroxide, and then heating to 60-80° C. to react for 4-5 hours, rotary evaporation, washing and drying to obtain a composite antistatic agent; Furthermore, in step A1, the ratio of γ-aminopropyltriethoxysilane, ethanol solution and pre-treated carbon black is 1-2 mL: 100 mL: 0.1-0.5 g, the ratio of nano carbon black and hydrogen peroxide solution in the pre-treated carbon black is 5 g: 100 mL, and the volume ratio of ethanol and deionized water in the ethanol solution is 9: 1; Further, in step A2, the dosage ratio of p-phenylenediamine, 2,5-diaminobenzoic acid, triethylamine, N,N-dimethylformamide, cyanuric chloride and modified carbon black is 0.08-0.12 mol: 0.15-0.25 mol: 15-45 mL: 300 mL: 0.05-0.15 mol: 1-2 g; Furthermore, in step A3, the usage ratio of carbon black / COF composite material, propylene oxide, tetrabutylammonium bromide, N,N-dimethylformamide, ethylene oxide and potassium hydroxide is 3-6 g: 5-9 g: 0.2-0.5 g: 100 mL: 8-12 g: 0.1-0.3 g.

[0006] The modified toughening agent is prepared by the following steps: Step B1, adding maleic anhydride grafted polyethylene and 5-aminoisophthalic acid into an internal mixer and mixing for 10-20 minutes, the conditions of the internal mixer are: a speed of 50-100 rpm, a mixing temperature of 120-140° C., to obtain grafted modified polyethylene; Step B2, adding cellulose and sodium hydroxide to deionized water for dispersion, stirring at 50-70° C. for 3-5 hours, centrifuging, washing, drying, and collecting the alkali-treated cellulose; then adding the alkali-treated cellulose and zinc chloride to the grafted modified polyethylene, maintaining the conditions of step B1 and continuing to blend for 15-25 minutes to obtain a modified toughening agent; Further, in step B1, the mass ratio of maleic anhydride grafted polyethylene to 5-aminoisophthalic acid is 10:0.5-1.5; Furthermore, in step B2, the mass ratio of alkali-treated cellulose, zinc chloride and maleic anhydride grafted polyethylene is 1-3:0.5-1.5:10, and the mass ratio of cellulose, sodium hydroxide and deionized water in the alkali-treated cellulose is 5:0.5-1.5:30.

[0007] A production process of antistatic polyolefin masterbatch comprises the following steps: Step S1, weighing raw materials by weight, adding polyolefin resin, composite antistatic agent, modified toughening agent, antioxidant and lubricant into a high-speed kneader, kneading for 25-35 minutes, and when the material temperature in the kneader rises to 100-120° C., discharging the material to obtain a mixed material; Step S2, putting the mixed material into a twin-screw extruder, extruding, cooling and pelletizing at a rotation speed of 150-300 rpm, a temperature of 70-90°C in zone 1, a temperature of 120-130°C in zone 2, a temperature of 135-145°C in zone 3 and a head temperature of 140-150°C, to obtain an antistatic polyolefin masterbatch.

[0008] Beneficial effects of the present invention: The polyolefin masterbatch in the present invention adopts polyolefin resin as the base resin, adds a composite antistatic agent to improve the antistatic performance of the masterbatch, and adds a modified toughening agent to improve the mechanical properties of the masterbatch; the composite antistatic agent adopts an organic-inorganic combination method to make the masterbatch have permanent antistatic performance; the modified toughening agent improves the mechanical properties of the masterbatch by modifying the maleic anhydride grafted polyethylene.

[0009] In the composite antistatic agent, nano carbon black is first treated with hydrogen peroxide, and then surface treated with a silane coupling agent to obtain modified carbon black; then, p-phenylenediamine, 2,5-diaminobenzoic acid and cyanuric chloride are used as organic ligands to load COF on the surface of the modified carbon black to synthesize a carbon black / COF composite material; finally, the carboxyl group on the surface of the composite material is reacted with propylene oxide and ethylene oxide to generate a composite antistatic agent containing a hydrophilic polyether segment. The carbon black, COF and polyether segments in the composite antistatic agent can work synergistically to improve the antistatic performance of the matrix; the composite material obtained by combining carbon black and COF acts as a conductive filler in the matrix and forms a conductive network in the matrix, thereby reducing the surface resistivity of the matrix, allowing the accumulated charges inside and on the surface of the matrix to be quickly released, thereby improving the antistatic performance of the matrix. At the same time, the composite material has better dispersibility than traditional carbon black and can be evenly dispersed in the matrix, further improving the antistatic performance of the matrix; the hydrophilic polyether segments in the composite antistatic agent can adsorb water molecules on the surface of the matrix to form a conductive water film, effectively reducing the surface resistivity of the matrix and reducing the possibility of static electricity accumulation, thereby achieving an antistatic effect. At the same time, the polyether segments can be used to migrate from the inside of the matrix to the surface of the matrix to compensate for the loss of the surface antistatic agent, making the antistatic performance of the matrix more durable, ensuring the continuity and stability of the antistatic effect, avoiding the loss of the surface antistatic agent caused by water washing or friction, and reducing the harm caused by static electricity.

[0010] In the modified toughening agent, maleic anhydride in maleic anhydride grafted polyethylene is firstly reacted with the amino group in 5-aminoisophthalic acid to obtain grafted modified polyethylene; then alkali-treated cellulose and zinc chloride are added to the grafted modified polyethylene for blending to obtain the modified toughening agent. The addition of the modified toughening agent improves the mechanical properties of the masterbatch; the addition of zinc chloride makes Zn 2+ It has a certain coordination effect with the polar groups in the grafted modified polyethylene and cellulose to form a Zn 2 + The metal coordination bond connecting the center enhances the interaction between the grafted modified polyethylene and cellulose, improves the toughness of the matrix, and thus improves the toughness of the masterbatch; in addition, hydrogen bonding can be formed between the grafted modified polyethylene and cellulose, and the hydrogen bonding can work synergistically with the metal coordination bond to dissipate the energy generated by external stretching, further improving the toughness of the masterbatch. DETAILED DESCRIPTION

[0011] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0012] The composite antistatic agent is prepared by the following steps: Step A1, disperse 5g of nano carbon black in 100mL of 30wt% hydrogen peroxide solution, and ultrasonically treat for 30min, then reflux and stir at 60°C for 24h, wash, dry, and collect the pre-treated carbon black; add 1mL of γ-aminopropyltriethoxysilane to 100mL of ethanol solution and ultrasonicate for 15min, then add 0.1g of pre-treated carbon black and ultrasonicate for 1.5h, then reflux and stir at 65°C for 5h, filter, wash, and dry to obtain modified carbon black, the volume ratio of ethanol to deionized water in the ethanol solution is 9:1; Step A2, 0.08 mol of p-phenylenediamine, 0.15 mol of 2,5-diaminobenzoic acid, and 15 mL of triethylamine were added to 300 mL of N,N-dimethylformamide and dispersed evenly, and then 0.05 mol of cyanuric chloride and 1 g of modified carbon black were added and ultrasonically dispersed for 30 min, and then transferred to an autoclave and reacted at 100 ° C for 10 h, washed and dried to obtain a carbon black / COF composite material; Step A3, disperse 3g of carbon black / COF composite material, 5g of propylene oxide and 0.2g of tetrabutylammonium bromide in 100mL of N,N-dimethylformamide, introduce nitrogen for 10min, react under nitrogen at 80°C for 2h, then cool to room temperature and add 8g of ethylene oxide and 0.1g of potassium hydroxide, then heat to 60°C and react for 4h, rotary evaporate, wash and dry to obtain a composite antistatic agent.

[0013] The modified toughening agent is prepared by the following steps: Step B1, adding 10g of maleic anhydride grafted polyethylene and 0.5g of 5-aminoisophthalic acid into an internal mixer and blending for 10min. The conditions of the internal mixer are: a speed of 50rpm and a mixing temperature of 120°C, to obtain grafted modified polyethylene; Step B2, 5 g of cellulose and 0.5 g of sodium hydroxide are dispersed in 30 g of deionized water, and stirred at 50° C. for 3 h, centrifuged, washed, and dried to collect the alkali-treated cellulose; then 1 g of alkali-treated cellulose and 0.5 g of zinc chloride are added to the grafted modified polyethylene, and the conditions of step B1 are maintained and blended for 15 min to obtain a modified toughening agent. Example

[0014] The composite antistatic agent is prepared by the following steps: Step A1, disperse 5g of nano carbon black in 100mL of 30wt% hydrogen peroxide solution, and ultrasonically treat for 45min, then reflux and stir at 60°C for 24h, wash, dry, and collect the pre-treated carbon black; add 1.5mL of γ-aminopropyltriethoxysilane to 100mL of ethanol solution and ultrasonicate for 15min, then add 0.3g of pre-treated carbon black and ultrasonicate for 2h, then reflux and stir at 70°C for 6h, filter, wash, and dry to obtain modified carbon black, wherein the volume ratio of ethanol to deionized water in the ethanol solution is 9:1; Step A2, 0.1 mol of p-phenylenediamine, 0.2 mol of 2,5-diaminobenzoic acid, and 30 mL of triethylamine were added to 300 mL of N,N-dimethylformamide and dispersed evenly, and then 0.1 mol of cyanuric chloride and 1.5 g of modified carbon black were added and ultrasonically dispersed for 30 min, and then transferred to an autoclave and reacted at 110° C. for 13 h, washed and dried to obtain a carbon black / COF composite material; Step A3, disperse 4.5g of carbon black / COF composite material, 7g of propylene oxide and 0.35g of tetrabutylammonium bromide in 100mL of N,N-dimethylformamide, introduce nitrogen for 10min, react under nitrogen at 85°C for 2.5h, then cool to room temperature and add 10g of ethylene oxide and 0.2g of potassium hydroxide, then heat to 70°C and react for 4.5h, rotary evaporate, wash and dry to obtain a composite antistatic agent.

[0015] The modified toughening agent is prepared by the following steps: Step B1, adding 10g of maleic anhydride grafted polyethylene and 1g of 5-aminoisophthalic acid into an internal mixer and blending for 15min, the conditions of the internal mixer are: speed of 100rpm, mixing temperature of 130°C, to obtain grafted modified polyethylene; Step B2, 5g of cellulose and 1g of sodium hydroxide are dispersed in 30g of deionized water, and stirred at 60°C for 4h, centrifuged, washed, dried, and the alkali-treated cellulose is collected; then 2g of alkali-treated cellulose and 1g of zinc chloride are added to the grafted modified polyethylene, and the conditions of step B1 are maintained and blended for 20min to obtain a modified toughening agent. Example

[0016] The composite antistatic agent is prepared by the following steps: Step A1, disperse 5g of nano carbon black in 100mL of 30wt% hydrogen peroxide solution, and ultrasonically treat for 60min, then reflux and stir at 60°C for 24h, wash, dry, and collect the pre-treated carbon black; add 2mL of γ-aminopropyltriethoxysilane to 100mL of ethanol solution and ultrasonicate for 15min, then add 0.5g of pre-treated carbon black and ultrasonicate for 2.5h, then reflux and stir at 75°C for 7h, filter, wash, and dry to obtain modified carbon black, wherein the volume ratio of ethanol to deionized water in the ethanol solution is 9:1; Step A2, 0.12 mol of p-phenylenediamine, 0.25 mol of 2,5-diaminobenzoic acid, and 45 mL of triethylamine were added to 300 mL of N,N-dimethylformamide and dispersed evenly, and then 0.15 mol of cyanuric chloride and 2 g of modified carbon black were added and ultrasonically dispersed for 30 min, and then transferred to an autoclave and reacted at 120° C. for 16 h, washed, and dried to obtain a carbon black / COF composite material; Step A3, disperse 6g of carbon black / COF composite material, 9g of propylene oxide and 0.5g of tetrabutylammonium bromide in 100mL of N,N-dimethylformamide, introduce nitrogen for 10min, react for 3h under nitrogen at 90°C, then cool to room temperature, add 12g of ethylene oxide and 0.3g of potassium hydroxide, then heat to 80°C and react for 5h, rotary evaporate, wash and dry to obtain a composite antistatic agent.

[0017] The modified toughening agent is prepared by the following steps: Step B1, adding 10g of maleic anhydride grafted polyethylene and 1.5g of 5-aminoisophthalic acid into an internal mixer and blending for 20min, the conditions of the internal mixer are: speed of 100rpm, mixing temperature of 140°C, to obtain grafted modified polyethylene; Step B2, 5g of cellulose and 1.5g of sodium hydroxide are dispersed in 30g of deionized water, and stirred at 70°C for 5h, centrifuged, washed, dried, and the alkali-treated cellulose is collected; then 3g of alkali-treated cellulose and 1.5g of zinc chloride are added to the grafted modified polyethylene, and the conditions of step B1 are maintained and blended for 25min to obtain a modified toughening agent. Example

[0018] A production process of antistatic polyolefin masterbatch comprises the following steps: 80 parts of polyethylene resin, 15 parts of the composite antistatic agent prepared in Example 1, 5 parts of the modified toughening agent prepared in Example 1, 1.5 parts of antioxidant 1010, and 2 parts of lubricant (polyethylene wax); Step S1, weighing raw materials by weight, adding polyethylene resin, the composite antistatic agent prepared in Example 1, the modified toughening agent prepared in Example 1, antioxidant 1010 and lubricant (polyethylene wax) into a high-speed kneader, kneading for 25 minutes, and when the material temperature in the kneader rises to 100° C., discharging the material to obtain a mixed material; Step S2, putting the mixed material into a twin-screw extruder, extruding, cooling and pelletizing at a rotation speed of 150 rpm, a temperature of zone 1 of 70° C., a temperature of zone 2 of 120° C., a temperature of zone 3 of 135° C. and a head temperature of 140° C., to obtain an antistatic polyolefin masterbatch. Example

[0019] A production process of antistatic polyolefin masterbatch comprises the following steps: 90 parts of polyethylene resin, 20 parts of the composite antistatic agent prepared in Example 2, 7 parts of the modified toughening agent prepared in Example 2, 2.5 parts of antioxidant 1010, and 3 parts of lubricant (polyethylene wax); Step S1, weighing raw materials by weight, adding polyethylene resin, the composite antistatic agent prepared in Example 2, the modified toughening agent prepared in Example 2, antioxidant 1010 and lubricant (polyethylene wax) into a high-speed kneader, kneading for 30 minutes, and when the material temperature in the kneader rises to 110° C., discharging the material to obtain a mixed material; Step S2, putting the mixed material into a twin-screw extruder, extruding, cooling and pelletizing at a rotation speed of 200 rpm, a temperature of zone 1 of 80°C, a temperature of zone 2 of 125°C, a temperature of zone 3 of 140°C and a head temperature of 145°C, to obtain an antistatic polyolefin masterbatch. Example

[0020] A production process of antistatic polyolefin masterbatch comprises the following steps: 100 parts of polyethylene resin, 25 parts of the composite antistatic agent prepared in Example 3, 10 parts of the modified toughening agent prepared in Example 3, 3.5 parts of antioxidant 1010, and 4 parts of lubricant (polyethylene wax); Step S1, weighing raw materials by weight, adding polyethylene resin, the composite antistatic agent prepared in Example 3, the modified toughening agent prepared in Example 3, antioxidant 1010 and lubricant (polyethylene wax) into a high-speed kneader, kneading for 35 minutes, and when the material temperature in the kneader rises to 120° C., discharging the material to obtain a mixed material; Step S2, putting the mixed material into a twin-screw extruder, extruding, cooling and pelletizing at a rotation speed of 300 rpm, a temperature of zone 1 of 90° C., a temperature of zone 2 of 130° C., a temperature of zone 3 of 145° C. and a head temperature of 150° C., to obtain an antistatic polyolefin masterbatch.

[0021] Comparative Example 1 This comparative example is a polyolefin masterbatch, which differs from Example 6 in that commercially available antistatic agent carbon black is used instead of the composite antistatic agent prepared in Example 3, and the rest are the same.

[0022] Comparative Example 2 This comparative example is a polyolefin masterbatch, which differs from Example 6 in that the modified toughening agent prepared in Example 3 is replaced by a commercially available toughening agent POE, and the rest are the same.

[0023] The polyolefin masterbatch prepared in Examples 4-6 and Comparative Examples 1-2 was mixed with polyethylene resin at a mass ratio of 1:8 to prepare test specimens. The specimen preparation process adopted an injection molding process, and the equipment adopted a twin-screw injection molding machine. The process parameters of the injection molding machine were: feeding section 100°C, compression section 170°C, homogenization section 190°C, injection die 185°C, and injection pressure 7MPa for performance testing: Notched impact strength test: Test the notched impact strength of the sample in accordance with GB / T 1043-1993 Hard Plastics Simple Supported Beam Impact Test Method; Tensile strength test: Test the tensile strength of the sample according to "GB / T 1040-1992 Plastic Tensile Test Method"; Surface resistivity test: Test the surface resistivity of the material according to GB / T 31838.3-2019 standard; The test results are shown in the following table:

[0024] As can be seen from the above table, after the mechanical properties test, the notched impact strength of the polyolefin masterbatch prepared by the present invention is 37KJ / m 2 -40KJ / m 2 The tensile strength is between 26MPa and 31MPa, indicating that the polyolefin masterbatch has excellent mechanical properties. After the surface resistivity test, the surface resistivity is between 9.2×10 7 Ω-5.4×10 8 Ω, indicating that the polyolefin masterbatch has excellent antistatic properties.

[0025] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. An antistatic polyolefin masterbatch, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of polyolefin resin, 15-25 parts of composite antistatic agent, 5-10 parts of modified toughening agent, 1.5-3.5 parts of antioxidant and 2-4 parts of lubricant; The polyolefin resin is polyethylene resin or polypropylene resin; The composite antistatic agent is prepared by the following steps: Step A1, dispersing nano carbon black in a 30wt% hydrogen peroxide solution, and ultrasonically treating it for 30-60min, then refluxing and stirring at 60°C for 24h, washing, drying, and collecting the pre-treated carbon black; adding γ-aminopropyltriethoxysilane to an ethanol solution and ultrasonically treating it for 15min, then adding the pre-treated carbon black and ultrasonically treating it for 1.5-2.5h, then refluxing and stirring it at 65-75°C for 5-7h, filtering, washing, and drying to obtain modified carbon black; Step A2, adding p-phenylenediamine, 2,5-diaminobenzoic acid and triethylamine to N,N-dimethylformamide and dispersing them uniformly, then adding cyanuric chloride and modified carbon black and ultrasonically dispersing them for 30 minutes, then transferring them to an autoclave and reacting them at 100-120° C. for 10-16 hours, washing and drying, to obtain a carbon black / COF composite material; Step A3, disperse the carbon black / COF composite material, propylene oxide and tetrabutylammonium bromide in N,N-dimethylformamide, introduce nitrogen for 10 minutes, react under nitrogen at 80-90°C for 2-3 hours, then cool to room temperature and add ethylene oxide and potassium hydroxide, then heat to 60-80°C and react for 4-5 hours, rotary evaporate, wash and dry to obtain a composite antistatic agent.

2. The antistatic polyolefin masterbatch according to claim 1, characterized in that: In step A1, the usage ratio of γ-aminopropyltriethoxysilane, ethanol solution and pre-treated carbon black is 1-2mL:100mL:0.1-0.5g, the usage ratio of nano carbon black and hydrogen peroxide solution in the pre-treated carbon black is 5g:100mL, and the volume ratio of ethanol and deionized water in the ethanol solution is 9:

1.

3. The antistatic polyolefin masterbatch according to claim 1, characterized in that: In step A2, the dosage ratio of p-phenylenediamine, 2,5-diaminobenzoic acid, triethylamine, N,N-dimethylformamide, cyanuric chloride and modified carbon black is 0.08-0.12 mol: 0.15-0.25 mol: 15-45 mL: 300 mL: 0.05-0.15 mol: 1-2 g.

4. The antistatic polyolefin masterbatch according to claim 1, characterized in that: In step A3, the usage ratio of carbon black / COF composite material, propylene oxide, tetrabutylammonium bromide, N,N-dimethylformamide, ethylene oxide and potassium hydroxide is 3-6g:5-9g:0.2-0.5g:100mL:8-12g:0.1-0.3g.

5. The antistatic polyolefin masterbatch according to claim 1, characterized in that: The modified toughening agent is prepared by the following steps: Step B1, adding maleic anhydride grafted polyethylene and 5-aminoisophthalic acid into an internal mixer and mixing for 10-20 minutes, the conditions of the internal mixer are: a speed of 50-100 rpm, a mixing temperature of 120-140° C., to obtain grafted modified polyethylene; Step B2, adding cellulose and sodium hydroxide to deionized water for dispersion, stirring at 50-70°C for 3-5h, centrifuging, washing, drying, and collecting the alkali-treated cellulose; then adding the alkali-treated cellulose and zinc chloride to the grafted modified polyethylene, maintaining the conditions of step B1 and continuing to blend for 15-25min to obtain a modified toughening agent.

6. The antistatic polyolefin masterbatch according to claim 5, characterized in that: In step B1, the mass ratio of maleic anhydride grafted polyethylene to 5-aminoisophthalic acid is 10:0.5-1.

5.

7. The antistatic polyolefin masterbatch according to claim 5, characterized in that: In step B2, the mass ratio of alkali-treated cellulose, zinc chloride and maleic anhydride grafted polyethylene is 1-3:0.5-1.5:10, and the mass ratio of cellulose, sodium hydroxide and deionized water in the alkali-treated cellulose is 5:0.5-1.5:

30.

8. The production process of the antistatic polyolefin masterbatch according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step S1, weighing raw materials by weight, adding polyolefin resin, composite antistatic agent, modified toughening agent, antioxidant and lubricant into a high-speed kneader, kneading for 25-35 minutes, and when the material temperature in the kneader rises to 100-120° C., discharging the material to obtain a mixed material; Step S2, putting the mixed material into a twin-screw extruder, extruding, cooling and pelletizing at a rotation speed of 150-300 rpm, a temperature of 70-90°C in zone 1, a temperature of 120-130°C in zone 2, a temperature of 135-145°C in zone 3 and a head temperature of 140-150°C, to obtain an antistatic polyolefin masterbatch.

Citation Information

Patent Citations

  • Conductive carbon black master batch and preparation method thereof

    CN118085436A

  • Molded article

    US20200224009A1

  • Halogen-free flame-retardant reinforced pet composite material and preparation method therefor

    WO2022068621A1